Development of Cooperative Contextual Reconstruction-Oriented Science Learning (KOKO) for Students with Special Needs - Wardana, Rendy Wikrama; Yanti, Fitri April; Ardina, Mona; Fitri, Elsi Adelia (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
Research in the background of limited research related to how to reconstruct science learning for students with special needs. The purpose of this study is to produce cooperative contextual reconstruction-oriented science learning (KOKO) for students with special needs. Research is a development research with ADDIE design (Analysis, Design and Develop). The population of this study was all students with special needs in special schools in South Bengkulu and North Bengkulu. Research instruments in the form of material and media expert validation questionnaires, teacher response questionnaires to the developed learning reconstruction, observation sheets and posttest questions to illustrate the structure of students' knowledge and science literacy. Data collection was carried out by providing validation questionnaires to material and media experts, providing teacher response questionnaires, making observations and giving posttest questions. Data analysis uses quantitative data analysis with descriptive statistics which are then narrated qualitatively. The results of the study resulted in KOKO learning design products including five stages, namely theme determination, contextual orientation, learning activities, evaluation, reflection and follow-up. The results of the product feasibility analysis showed an average validation result with a score of 0.85 in the very decent category